Biznesa korespondences nosacījumi un to atšķirības angļu, krievu un latviešu valodās - Saļikova, Jeļizaveta (Latvijas Universitāte, 2007)
Šis pētījums ir veltīts angļu, krievu un latviešu biznesa vēstuļu struktūru analīzei, aplūkojot struktūrelementu izkārtojuma principus. Šis darbs izpēta angļu, krievu un latviešu vēstuļu stilu, kas pamatojas uz dažādiem retoriskiem aspektiem. Pētījuma mērķis ir sistemātiski salīdzināt angļu, krievu un latviešu biznesa korespondences nosacījumus, lai atklātu to līdzības un atšķirības. Darba metodes ietvēra no dažādu avotu saņemtas informācijas apkopošanu un sistematizāciju, kas arī terminoloģijas izpēti un unificēšanu salīdzinošās analīzes nolūkam. Pētījuma rezultāti liecina, ka pastāv gan līdzības, gan atšķirības angļu, krievu un latviešu biznesa korespondences nosacījumos. Pēdējo var izskaidrot ar atšķirībām retoriskajās tradīcijās, kā arī atbilstošo valodu struktūru atšķirībām.

The present research deals with the investigation of the structural framework of a typical English, Russian and Latvian business letter, discussing the main principles of structural elements’ arrangement, as well as the characteristic features of English, Latvian and Russian business letters’ style based on various rhetorical aspects. The purpose of the research was to make a systematic comparison of English, Latvian and Russian business style conventions in order to reveal their similarities and differences. The methods of research included processing and systematization of the data provided by the sources, which also involved the analysis of their terminology and its unification for the purposes of comparative analysis. The results obtained have revealed that there are both similarities and differences in English, Russian and Latvian business letters style conventions. The latter can be explained either by the differences in the rhetorical traditions or by the differences in the structure of the respective languages.
Business Correspondence Conventions – Differences in English/ Russian/ Latvian
Keywords: Filoloģija